2020
DOI: 10.2147/cmar.s232632
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of BRMS1L as Metastasis Suppressing Gene in Esophageal Squamous Cell Carcinoma</p>

Abstract: Introduction: Breast cancer metastasis suppressor 1 like (BRMS1-like)was first reported to be a component of the Sin3-HDAC complex, but the role in the progression of cancers was largely unknown. Our previous study reported that BRMS1L promoted the metastasis of breast cancer through facilitating the recruitment of HDAC complex to the promoter FZD10, and hence suppressing the transcription of FZD10. Methods: In this study, we detected the expression level of BRMS1L in esophageal squamous cell carcinoma (ESCC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…BRMS1L knockdown increased levels of expression of FZD10 and induced EMT [ 105 ]. This mechanism also functions in esophageal squamous cell carcinoma [ 108 ]. In colorectal cancer (CRC), cells with high FZD10 expression were more efficient than cells with low FZD10 at stimulating EMT [ 134 ].…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…BRMS1L knockdown increased levels of expression of FZD10 and induced EMT [ 105 ]. This mechanism also functions in esophageal squamous cell carcinoma [ 108 ]. In colorectal cancer (CRC), cells with high FZD10 expression were more efficient than cells with low FZD10 at stimulating EMT [ 134 ].…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…BRMS1L and p53 colocalize in cancer cells and synergistically inhibit the migration and invasion of cancer cells. BRMS1L also suppresses oesophageal squamous cell carcinoma metastasis by suppressing ITGA7 expression and is regulated by the transcription of CBP/P300 [12] . In addition, our previous papers have confirmed that BRMS1L inhibits EMT of tumour cells through the classical WNT-β-catenin signalling pathway, thereby preventing ovarian cancer metastasis [21] .…”
Section: Discussionmentioning
confidence: 99%
“…used immunohistochemical staining to reveal that BRMS1L shows high expression in normal breast tissues and low expression in breast cancer, and its expression is gradually decreased and lost in accordance with distant metastasis of breast cancer [11] . In addition, low expression of BRMS1L has also been found in several other malignant tumours [12] , [13] , [14] , [15] , [16] . Functional experiments in breast cancer revealed that BRMS1L affects the invasion and migration capabilities of breast cancer cells by inhibiting EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Relative gene expression was analyzed by the 2-ΔΔCt method, using Gapdh as an internal control. qPCR and in vitro cancer cell function assays were also performed as described previously [ 33 , 34 ]. qPCR primer sequences are shown in Additional file 1 : Table S3.…”
Section: Methodsmentioning
confidence: 99%